Оздоби українського короваю: типи, художні ознаки, символіка - Герус, Л. (Інститут народознавства НАН України, 2008)
The article deals with ornamentation of Ukrainian Korovai bread laid upon loaves after the baking of ones. Under consideration are put some elements of floral origin (twigs, leaves, flowers, fruits of growth) as well as those of animal (feather), elements of objective world (bands, towels, spoons, candles) and especially produced elements (flowers, bands cut of paper, foil or silk). Symbolism of decorations is being analyzed. Changes in ordering and composition of decorations upon Korovais and in symbolic conceptualization of ones through the late XIX to early XX cc. are being traced in this study.